A theoretical formulation of the buckling analysis of a composite sandwich structure with multiple holes. (February 2022) - Kim, Yongha; Park, Jungsun
This article presents a theoretical formulation presented for conducting a buckling analysis of the composite sandwich plate with multiple holes via the homogenization method. The validity of the theoretical formulation was verified by comparing the results of the finite element analysis and experimental analysis. Finally, the theoretical formulation was used to optimize a composite sandwich plate with multiple holes for the design of an aircraft structure to minimize the mass. The optimization result allows a database to be obtained on the buckling characteristics of composite sandwich structures with multiple holes for applying aerospace applications. We then concluded that the theoretical formulation is well-suited to buckling analysis of a composite sandwich structure with multiple holes for aerospace applications due to their relative simplicity and computational efficiency.